Alteration of Masquelet's induced membrane characteristics by different kinds of antibiotic enriched bone cement in a critical size defect model in the rat's femur. Issue 2 (February 2016) - Nau, Christoph; Seebach, Caroline; Trumm, Alexander; Schaible, Alexander; Kontradowitz, Kerstin; Meier, Simon; Buechner, Hubert; Marzi, Ingo; Henrich, Dirk
Abstract: The Masquelet technique for the treatment of large bone defects consists of a 2-stage procedure. In the first stage, a polymethylmethacrylate (PMMA) cement spacer is inserted into the bony defect of a rat's femur and over a period of 2–4 weeks a membrane forms that encapsulates the defect/spacer. In a second operation the membrane is opened, the PMMA spacer is removed and the resulting cavity is filled with autologous bone. Different kinds of bone cements are available, with or without supplemental antibiotics. Both might influence the development and the characteristics of the induced membrane which might affect the bone healing response. Hence, this comparative study was performed to elucidate the effect of different bone cements with or without supplemental antibiotics on the development of an induced membrane in a critical size femur defect model in rats. A total of 72 male SD rats received a 10 mm critical size defect of the femur which was stabilised by a plate osteosynthesis and filled with either Palacos + Gentamycin, Copal Gentamycin + Vancomycin, Copal + Gentamycin + Clindamycin or Copal Spacem. The induced membranes were analysed after two, four and six weeks (wks) after insertion of the cement spacers ( n  = 6/group). Paraffin embedded histological sections of the membrane were microscopically analysed for membrane thickness, elastic fibres, vascularisation and proliferation by an independent observer blinded to the group setup. The thickness of the induced membrane increased significantly from 2 wks (553 μm) to 6 wks (774 μm) in group Palacos + Gentamycin whereas membrane thickness decreased significantly in groups Copal + Gentamycin + Clindamycin (682–329 μm) and Copal Spacem (916 μm to 371 μm). The comparison between the groups revealed significantly increased membrane thickness in group Palacos + Gentamycin and Copal Gentamycin + Vancomycin in comparison to group Copal + Gentamycin + Clindamycin six weeks after induction. However, the fraction of elastic fibres was significantly increased in groups Copal + Gentamycin + Clindamycin (71%, 80%) and Copal Spacem (82%, 81%) after 2 and 4 weeks in comparison to the groups Palacos + Gentamycin (56%, 57%) and Copal Gentamycin + Vancomycin (63%, 69%). Those differences however were partly diminished after 6 wks. The ratio of immature (vWF+) to more mature (CD31+) blood vessels increased significantly in groups Palacos + Gentamycin and Copal Gentamycin + Vancomycin whereas no significant alterations were noted in groups Copal + Gentamycin + Clindamycin and Copal Spacem. For the first time we demonstrated that thickness and proportion of elastic fibres in induced membranes were influenced by the type of cement and the kind of supplemental antibiotics being used. Whether these alterations of the induced membrane have an effect on bone healing remains to be proven in future studies.